Application of VEGFA and FGF-9 enhances angiogenesis, osteogenesis and bone remodeling in type 2 diabetic long bone regeneration - Wallner, Christoph; Wagner, Johannes Maximilian; Schulte, Matthias; Fischer, Sebastian; Richter, Wiltrud; Kneser, Ulrich (PLOS ONE, 2015)
Although bone regeneration is typically a reliable process, type 2 diabetes is associated with impaired or delayed healing processes. In addition, angiogenesis, a crucial step in bone regeneration, is often altered in the diabetic state. In this study, different stages of bone regeneration were characterized in an unicortical bone defect model comparing transgenic type 2 diabetic (db-/db-) and wild type (WT) mice in vivo. We investigated angiogenesis, callus formation and bone remodeling at early, intermediate and late time points by means of histomorphometry as well as protein level analyses. In order to enhance bone regeneration, defects were locally treated with recombinant FGF-9 or VEGFA. Histomorphometry of aniline blue stained sections indicated that bone regeneration is significantly decreased in db-/db- as opposed to WT mice at intermediate (5 days post operation) and late stages (7 days post operation) of bone regeneration. Moreover, immunohistochemical analysis revealed significantly decreased levels of RUNX-2, PCNA, Osteocalcin and PECAM-1 in db-/db- defects. In addition, osteoclastogenesis is impaired in db-/db- indicating altered bone remodeling. These results indicate significant impairments in angiogenesis and osteogenesis in type 2 diabetic bones. Importantly, angiogenesis, osteogenesis and bone remodeling could be reconstituted by application of recombinant FGF-9 and, in part, by VEGFA application. In conclusion, our study demonstrates that type 2 diabetes affects angiogenesis, osteogenesis and subsequently bone remodeling, which in turn leads to decreased bone regeneration. These effects could be reversed by local application of FGF-9 and to a lesser degree VEGFA. These data could serve as a basis for future therapeutic applications aiming at improving bone regeneration in the type 2 diabetic patient population.